Wordsworth's Biblical Ghosts - Westbrook, D. author. aut Link
XI, 244 p.
Keywords: The Bible serves Wordsworth as a basis for his poetry and poetics, providing language, images, figures, and importantly, a paradigm of poetic genres. Working from three interrelated critical approaches - intertextuality, poetics, and metaphysics - Westbrook first analyzes Wordsworth's theory and practice as these reflect the New Testament doctrine of the Incarnation. Subsequent chapters consider Wordsworth's adaptation of biblical narrative forms - etymological tales, parables, and mystical allegories. Closing chapters examine some extraordinary linguistic innovations in Wordsworth's revisions of biblical apocalypse, techniques that permit the poet to express the ineffable and to reveal nothing.